Characteristics of sports and recreation-related emergency department visits among school-age children and youth in North Carolina, 2010-2014 - Katherine J. Harmon; Scott K. Proescholdbell; Johna Register-Mihalik; David B. Richardson; Anna E. Waller; Stephen W. Marshall (BMC, 2018)
Abstract Background Sports and recreational activities are an important cause of injury among children and youth, with sports-related traumatic brain injuries (TBIs) being of particular concern given the developing brain. This paper reports the characteristics of sport and recreation-related (SR) emergency department (ED) visits among school-age children and youth in a statewide population. Methods This study included all injury-related visits made to all North Carolina 24/7 acute-care civilian hospital-affiliated EDs by school-age youth, 5-18 years of age, during 2010-2014 (N = 918,662). Population estimates were based on US decennial census data. Poisson regression methods were used to estimate incidence rates and rate ratios. Results During the five-year period, there were 767,075 unintentional injury-related ED visits among school-age youth, of which 213,518 (27.8%) were identified as SR injuries. The average annual absolute number and incidence rate (IR) of SR ED visits among school-age youth was 42,704 and 2374.5 ED visits per 100,000 person-years (95% confidence interval [CI], 2364.4-2384.6), respectively. In comparison to other unintentional injuries among school-age youth, SR ED visits were more likely to be diagnosed with an injury to the upper extremity (Injury Proportion Ratio [IPR] = 1.28; 95% CI, 1.27-1.29), the lower extremity (IPR = 1.14; 95% CI, 1.13-1.15), and a TBI or other head/neck/facial injury (IPR = 1.12; 95% CI, 1.11-1.13). Among ED visits made by school-age youth, the leading cause of SR injury was sports/athletics played as a group or team. The leading cause of team sports/athletics injury was American tackle football among boys and soccer among girls. The proportion of ED visits diagnosed with a TBI varied by age and sex, with 15-18 year-olds and boys having the highest population-based rates. Conclusions Sports and recreational activities are an important component of a healthy lifestyle, but they are also a major source of injury morbidity among school-age youth. Physical activity interventions should take into account sex and age differences in SR injury risk.